What are the drivers of tax capacity in sub-Saharan Africa? - Abrams Mbu Enow Tagem; Oliver Morrissey (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
There is limited research on the underlying institutional framework of tax policy and capacity: how tax collection efficiency changes over time and the importance of institutional factors in this process. This paper fills this gap by devising a measure of tax capacity distinct from commonly used measures of tax effort based on residuals from a tax performance (tax/gross domestic product ratio) regression. The paper uses annual data on 44 sub-Saharan African countries covering the period from 1980 to 2018. The empirical strategy separating performance from underlying fiscal capacity proceeds in three steps: estimating standard tax performance regressions, from which we generate measures of potential and actual tax revenue; decomposing the actual-to-potential tax revenue ratio to use the trend component as a measure of tax capacity; and applying general-to-specific analysis with a wide variety of economic and institutional variables as potential determinants of tax capacity to identify the most important correlates.
Keywords: C23; H20; O23; O43; 330; tax capacity; tax performance; general-to-specific; institutional variables